Estresse oxidativo em ovinos das raças Suffolk e Santa Inês experimentalmente infectados por Haemonchus contortus - Baptistiolli, Lillian [UNESP] (2014)
There are some little evidence that tissue damage caused by gastrointestinal parasites in sheep promote oxidative stress, but the mechanisms that cause the imbalance between oxidants and antioxidants are not well established. This study aimed to prove the hypothesis that oxidative stress occurs in sheep infected with Haemonchus contortus and that this varies with racial resistance. Therefore, we investigated the relationship between oxidative stress caused by infection with H. contortus, the parasite load, anemia and hypoalbuminemia. To this end, Suffolk sheep breed (n = 15) and Santa Inês (n = 22) were wormed and after confirmed the absence of eggs in the feces (day 0), all animals were infected orally with 5000 third-stage larvae (L3) from H. contortus. The number of eggs per gram of feces (EPG) and the concentration of different plasma markers of oxidative stress (lipid peroxidation, albumin, uric acid, total bilirubin, total antioxidant capacity, total oxidant concentration and oxidative stress index) were quantified before (day 0) and 28, 32 and 42 days of experimental infection in both breeds. The amendments to the post-infection oxidative stress biomarkers varied with the race, having in common Suffolk and Santa Inês sheep the total oxidant concentration (TOC) increase on the 28th, followed by an increase of TAC on day 42. Breed Sheep Suffolk had higher parasite burden in all post-infection times, and this race the OPG correlated with the TOC (r = 58; p <0.02) and Santa Ines the OPG correlated with bilirubin (r = 0.49; p <0.02). The amendments to the post-infection oxidative stress markers were not associated with anemia and hypoalbuminemia. During the first 42 days post-infection with H. contortus, oxidative stress index varied according to race, in part due to increased oxidant production probably caused by tissue injury and also because of a probable compensatory ... (Complete abstract electronic access below)